Sistem Informasi Pengurusan Surat Pengantar Berbasis Framework Codeigniter Guna Meningkatan Kualitas Pelayanan kepada Masyarakat - Andesita Prihantara; Abdul Aziz (Politeknik Harapan Bersama, 2018)
The guide letter has an important role in the administration of population administration at the village level. The letter of introduction is a proof of recognition from the Chairman of RT, RW and Village Office Chairman against the residents domiciled in the area. The management of guide letter and residents' domicile data in Bandasari Village has not been well managed. The data of introductory letters and immigrants are still managed and stored in each Chariman RT. In this research, developed Information System of Guidance Letter Handling Village Management Bandasari aims to manage data introduction letter and data of immigrants in the village Bandasari. System development using System Development Life Cycle (SDLC) method with waterfall process model and blackbox testing method. Based on the tests conducted, it is known that the system will be developed to assist fast the People, Chairman of RT, RW and Village chief in managing the data of guidace letters and migrant residents data, because data saved in one database and can be access by user.